Combined transplantation of autologous hematopoietic stem cells and allogenic mesenchymal stem cells increases T regulatory cells in systemic lupus erythematosus with refractory lupus nephritis and leukopenia. (October 2015) - Wang, Q; Qian, S; Li, J; Che, N; Gu, L; Wang, Q; Liu, Y; Mei, H
Autologous hematopoietic stem cell (HSC) and mesenchymal stem cell (MSC) transplantation is currently being evaluated as a novel treatment for autoimmune diseases, such as systemic lupus erythematosus (SLE). Here we report a case of autologous HSC transplantation combined with MSCs in a 25-year-old severe SLE patient with multiple life-threatening complications and refractory to conventional cyclophosphamide (CYC) therapy. After being pretreated with CYC, ﬂudarabine and antithymocyte globulin, the patient was transplanted with autologous CD34+HSCs and MSCs by intravenous infusion. Hematopoietic regeneration was observed on day 12 thereafter. After HSC and MSC transplantation, the patient's clinical symptoms caused by SLE were remitted, and the SLEDAI score decreased. Moreover, CD4+CD25+FoxP3+Treg cells increased in peripheral blood mononuclear cells (PBMCs) after transplantation. This result suggests that the combined transplantation of HSCs and MSCs may reset the adaptive immune system to re-establish self-tolerance in SLE. A 36-month follow-up showed that the clinical symptoms remained in remission. Although a longer follow-up is required for assessing the long-term efficacy, our present results suggest that the combined transplantation of HSCs and MSCs may be a novel and effective therapy for refractory SLE.